2021
DOI: 10.3390/plants10071457
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Mild Salinity Conditions and Exogenously Applied Phenolics Modulates Functional Traits in Lettuce

Abstract: The quest for sustainable strategies aimed at increasing the bioactive properties of plant-based foods has grown quickly. In this work, we investigated the impact of exogenously applied phenolics, i.e., chlorogenic acid (CGA), hesperidin (HES), and their combinations (HES + CGA), on Lactuca sativa L. grown under normal- and mild-salinity conditions. To this aim, the phenolic profile, antioxidant properties, and enzyme inhibitory activity were determined. The untargeted metabolomics profiling revealed that lett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
5
11
0
Order By: Relevance
“…In this line, Wang et al (2014) reported that exogenous CA applied to apple fruits provoked an increase in the activity of phenylalanine ammonia lyase (PAL) and cinnamate-4-hydrolase (C4H) and a decrease in polyphenol oxidase (PPO) and peroxidase (POD) [21]. The accumulation of phenolics following exogenous application of CA is also in agreement with our previous results [24]. Our current findings strengthen the ability of CA and, to a lesser extent, HES + CA to enhance the accumulation of phenylpropanoids.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this line, Wang et al (2014) reported that exogenous CA applied to apple fruits provoked an increase in the activity of phenylalanine ammonia lyase (PAL) and cinnamate-4-hydrolase (C4H) and a decrease in polyphenol oxidase (PPO) and peroxidase (POD) [21]. The accumulation of phenolics following exogenous application of CA is also in agreement with our previous results [24]. Our current findings strengthen the ability of CA and, to a lesser extent, HES + CA to enhance the accumulation of phenylpropanoids.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, plants exposed to combined CA and HES can provide complementary and synergic effects. Indeed, our previous work [24] showed that CA, HES, and their combination modulated the functional traits of lettuce in a distinctive manner.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In particular, Zhang et al [75] showed that the addition of chlorogenic acid and hesperidin alleviates the impact of salt stress by improving photosynthetic performance. Moreover, Zhang et al [76] pointed out that the addition of phenolics, including hesperidin, can modulate functional traits in lettuces, also modifying the endogenous phenolic content. In this sense, hesperidin has been found to be the most abundant flavone in duckweed extracts [26].…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic profiles of different D. maritima extracts were analyzed using a UHPLC-QTOF-MS (Agilent Technologies, Stevens Creek Blvd, Santa Clara, CA, USA). The instrument parameters and methods adopted for the analysis were optimized in previous works [ 66 , 67 ]. Regarding chromatographic separation, it was achieved by using an Agilent InfinityLab Poroshell 120 pentafluorophenyl (PFP) column (2.1 × 100 mm, 1.9 μm) (Agilent Technologies, Stevens Creek Blvd, Santa Clara, CA, USA) and a binary mixture of water and acetonitrile acidified with 0.1% ( v / v ) formic acid as mobile phase (LC-MS grade, VWR, Milan, Italy).…”
Section: Methodsmentioning
confidence: 99%